The structural characteristics of world trade and the merchandise exports of Serbia - Kovačević Radovan (Ekonomski Anali, 2009)
This paper analyses the world merchandise trade structure and the structure of Serbian merchandise exports. The analysis shows that the prominent characteristic of post-World War II world trade is more dynamic growth in the volume of manufactured goods as compared to agricultural goods. Due to the lessening share of agricultural products world merchandise trade has decreased and rapid industrialization has been fostered in developing countries. An increased share for developing countries followed the developed countries' decreasing share in world manufacturing trade. The developing countries' increased share was strongest in telecom and office equipment exports. These sectors are characterized by production fragmentation, which is being realized by transnational companies. Serbia, like the other South East European countries, has not yet managed to significantly integrate into international production networks. Serbia's most important exports are manufactured products with a low level of added value . In addition, Serbia still has a high share of primary products in its exports. A higher share of exports of goods and services in the gross domestic products (GDP) cannot be achieved without increasing imports of new technologies and equipment, i.e. without a higher investment share of the GDP. The main conclusion of this article is that the creation of a favorable investment climate and an increase in Serbia's international credit rating are the preconditions for stronger foreign direct investment (FDI), which would be the main channel for restructuring in the real sector. Creation of new small and medium enterprises (SMEs) through greenfield investment and their integration into the international production networks is the starting point for the restructuring of Serbian industrial production and merchandise export, i.e. the way of increasing the share of merchandise exports in the GDP.